English literature and ancient languages - Haynes, Kenneth 1966- (Oxford University Press, 2003)
Literature in English is hardly ever entirely in English. Contact with other languages takes place, for example, whenever foreign languages are introduced, or if a native style is self-consciously developed, or when aspects of English are remade in the image of another language. Since the Renaissance, Latin and Greek have been an important presence in British poetry and prose. This is partly because of the importance of the ideals and ideologies founded and elaborated on Roman and Greek models. Latin quotations and latinate English have always been ways to represent, scrutinise, or satirize the influential values associated with Rome. The importance of Latin and Greek is also due to the fact that they have helped to form and define a variety of British social groups. Lawyers, Catholics, and British gentlemen invested in Latin as one source of their distinction from non-professionals, from Protestants, and from the unleisured. British attitudes toward Greek and Latin have been highly charged because the animus that existed between groups has also been directed toward these languages themselves. This book is a study of literary uses of language contact, of English literature in conjunction with Latin and Greek. While the book's emphasis is literary, that is formal and verbal, its goal is to discover how social interests and cultural ideas are, and are not, mediated through language.